2014
DOI: 10.1016/j.jpowsour.2014.08.126
|View full text |Cite
|
Sign up to set email alerts
|

A dual pore carbon aerogel based air cathode for a highly rechargeable lithium-air battery

Abstract: International audienceCathode structure plays a vital role in lithium-air battery for that it can provide space for discharged products accommodation and free path for oxygen, e− and Li+ transport. However, pore blockage, cathode passivation and degradation all result in low discharge rates and poor cycling capability. To get rid of these predicaments, a novel highly conductive dual pore carbon aerogel based air cathode is fabricated to construct a lithium-air battery, which exhibits 18 to 525 cycles in the Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…In addition, introducing catalysts or "promoters" into the cathodes of LieO 2 batteries has been reported as a mean to reduce the battery polarization [19,26,27]. Compared with conventional solid catalysts (precious metals, transitional oxides etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, introducing catalysts or "promoters" into the cathodes of LieO 2 batteries has been reported as a mean to reduce the battery polarization [19,26,27]. Compared with conventional solid catalysts (precious metals, transitional oxides etc.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported an increase in the specific energy of these batteries with increasing carbon mesopore volume in the air electrode. [24][25][26] In this sense, several approaches can be defined to improve oxygen diffusion across the electrode: (i) reduction of the electrode thickness in order to minimize the diffusion distance, and (ii) minimization of electrode pore overflow to allow the diffusion of oxygen.…”
mentioning
confidence: 99%
“…All of the specific capacities are calculated by dividing the charge amount by active material weight, that is the sum of carbonaceous support and electrocatalytic nanopowders, when present. GDE-H ( Figure 5 a, Curve 2) and GDE-M ( Figure 5 a, Curve 3), exploiting HCMSC and MCC carbon matrices, respectively, behave better than either the reference cathodes or the newly-proposed material, like graphene [ 47 , 48 ]. MCC allows reaching a specific capacity of 1560 mAh·g −1 , while the HCMSC-based cathode gives 1150 mAh·g −1 .…”
Section: Resultsmentioning
confidence: 99%